2020
DOI: 10.3390/ijms21051767
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Radio-Resistance Using the Optimization of Radiotherapy

Abstract: Radiotherapy is an essential component of cancer therapy and remains one of the most (cost-) effective treatment options available [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Radiotherapy is an effective treatment for unresectable lung cancer [ 14 ] that plays an important role in the clinical management of lung cancer patients. However, not all patients can benefit from radiotherapy because of cancer cell resistance [ 15 ]. In our study, significant OS outcome differences were observed between different GCNT3 expression groups after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is an effective treatment for unresectable lung cancer [ 14 ] that plays an important role in the clinical management of lung cancer patients. However, not all patients can benefit from radiotherapy because of cancer cell resistance [ 15 ]. In our study, significant OS outcome differences were observed between different GCNT3 expression groups after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, radio-resistance inherent in various cancers (e.g., CRC and lung cancer) leads to poor response of multiple malignant patients initially. [117][118][119][120][121] Besides, owing to physical barriers, such as BBB, major therapeutic molecules fail to exert antitumor effects with irradiation spontaneously in GBM. 122,123 Given the above limitation, it is time for engineered exosomes to make their way into history.…”
Section: Radiotherapymentioning
confidence: 99%
“…Radiotherapy is an effective method of cancer treatment, but the resistance and side effects of radiation therapy affect its efficacy. Therefore, sensitizers that kill tumor cells improve the efficacy of radiotherapy ( Chevalier 2020 ). Tan IIA combined with irradiation reduces histone H3 (S10) phosphorylation in ionizing radiation-resistant cell lines (CAL27-IR and SCC25-IR cells), and this combination enhances irradiation-induced DNA damage and promotes apoptosis, thereby inhibiting tumor growth in vivo and in vitro ( Li et al, 2021 ).…”
Section: Future Prospectsmentioning
confidence: 99%